Exploring academic dishonesty in the Middle East: a qualitative analysis of students’ perceptions - Aljurf, S.; Kemp, L.; Williams, John (Routledge, 2019)
Most previous studies of academic dishonesty have been conducted in North America and Europe, and have focused on the contextual, institutional, and individual factors that influence students’ propensity to cheat. While such studies offer useful background and structure to this endemic problem, this study aimed to gain deeper insights into student perceptions of academic dishonesty in a multi-cultural context. Our study sample was sourced from a large private university based in the United Arab Emirates, in which there is a culturally diverse mix of national and international students (Arab and non-Arab). From our data, while a number of student perceptions were similar to those reported in other studies, several new socio-cultural themes emerged. In particular, Arab students perceived: peer student obligations; patriarchal pressure; shame avoidance; and a Fahlawi [Fahlawi–derives from ‘fellahin’ or quick-witted individual. This Arab cultural term references a person with a highly adaptive attitude and an ability to achieve things with minimal effort] mind-set, as being influential on their academic dishonesty attitudes and behaviours.